2014
DOI: 10.1007/978-3-319-13416-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Review of Trends in Mobile Learning Studies in Mathematics: A Meta-Analysis

Abstract: Abstract. The field of mobile learning is growing an exponential rate. To best understand this field, it is crucial to gain a collective understanding of the research that has taken place. There are a number of recent studies which looked at collective trends in mobile learning across subjects. However, these results do not provide insight into specific subject areas. This meta-analysis reveals the trends in mobile learning in mathematics with a comprehensive analysis and synthesis of 48 studies from the year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It has been found that the spread of mobile phone apps is very common in various university context specifically university primary studies. The study has also found that most previous studies and researches had focused on designing mobile learning systems while there is a necessity to conduct the effects of mobile learning (Crompton and Burke, 2014).…”
Section: E-learning and M-learningmentioning
confidence: 89%
“…It has been found that the spread of mobile phone apps is very common in various university context specifically university primary studies. The study has also found that most previous studies and researches had focused on designing mobile learning systems while there is a necessity to conduct the effects of mobile learning (Crompton and Burke, 2014).…”
Section: E-learning and M-learningmentioning
confidence: 89%
“…Mobile technologies have provided various approaches to learning: engaging learners in contextualised learning environments using the plethora of sensors built-in on these mobile technologies (Tangney, Weber, Knowles, Munnelly, Watson, Salkham and Jennings, 2010) using the mobile phone to journal math learning (Project Tomorrow, 2011); and connecting learners through mobile phones and social media (Roberts, 2009). Crompton & Burke's (2014) survey of mobile learning in mathematics showed that there is a growing interest in terms of its effectiveness and that 75% out of the 48 studies reported positive learning outcomes. However, this number is rather small in comparison to the amount of research that utilised other existing educational technologies like computers and calculators.…”
Section: Reports On the Use Of Mobile Learning In Mathematicsmentioning
confidence: 99%
“…For example, in one of these studies, mobile learning studies on mathematics between 2000 and 2014 were examined by meta-analysis method. In this study, which was reviewed by 48 studies, it was concluded that interest in mobile learning has increased over the years and mobile learning has become more common due to the development of technology [10].…”
Section: Related Researchmentioning
confidence: 99%